Bone Marrow T Cells and the Integrated Functions of Recirculating and Tissue-Resident Memory T Cells - Di Rosa, Francesca; Gebhardt, Thomas (Frontiers in Immunology, 2016)
Changes in T cell trafficking accompany the naïve to memory T cell antigen-driven differentiation, which remains an incompletely defined developmental step. Upon priming, each naïve T cell encounters essential signals–i.e. antigen, co-stimuli and cytokines– in a secondary lymphoid organ; nevertheless its daughter effector and memory T cells recirculate and receive further signals during their migration through various lymphoid and non-lymphoid organs. These additional signals from tissue microenvironments have an impact on immune response features, including T cell effector function, expansion and contraction, memory differentiation, long-term maintenance and recruitment upon antigenic re-challenge into local and/or systemic responses. The critical role of T cell trafficking in providing efficient T cell memory has long been a focus of interest. It is now well recognized that naïve and memory T cells have different migratory pathways, and that memory T cells are heterogeneous with respect to their trafficking. We and others have observed that, long time after priming, memory T cells are preferentially found in certain niches such as the bone marrow or at the skin/mucosal site of pathogen entry, even in the absence of residual antigen. The different underlying mechanisms and peculiarities of resulting immunity are currently under study. In this review, we summarize key findings on bone marrow and tissue-resident memory T cells and revisit some issues in memory T cell maintenance within such niches. Moreover, we discuss bone marrow seeding by memory T cells in the context of migration patterns and protective functions of either recirculating or tissue-resident memory T cells.